1998
DOI: 10.1017/s0007114598001810
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of increased intake of saturated fat and cholesterol on atherosclerosis in the Japanese quail (Coturnix japonica)

Abstract: Increasing the energy value of diets with dietary fat, particularly fats rich in saturated fatty acids, can result in the elevation of plasma total and lipoprotein cholesterol. In the present study, experimental diets were designed to examine the effects of increasing the energy content of diets with a saturated fat source and cholesterol in a non-purified diet on hyperlipoproteinaemia and aortic plaque composition in the atherosclerosis-susceptible Japanese quail (Coturnix japonica) model of human atheroscler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Plasma cholesterol is one blood lipid fraction (Bell & Sturkie 1965) and captive and free-ranging studies have reported that birds fed with dietary cholesterol show significantly increased the PC levels (Gavett & Wakeley 1986;Yuan et al 1997Yuan et al , 1998Eder 1999).…”
Section: Blood Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma cholesterol is one blood lipid fraction (Bell & Sturkie 1965) and captive and free-ranging studies have reported that birds fed with dietary cholesterol show significantly increased the PC levels (Gavett & Wakeley 1986;Yuan et al 1997Yuan et al , 1998Eder 1999).…”
Section: Blood Parametersmentioning
confidence: 99%
“…For example, a cholesterol-rich diet facilitated the development of atherosclerotic plaque in Japanese quail (Coturnix japonica) (Yuan et al 1997(Yuan et al , 1998 and increased the concentrations of cholesterol in the liver (Eder 1999 in cross-bred geese; Yuan et al 1999 in Japanese quail). There is a possibility of similar effects among fed magpies if the influence of feeding at plasma level that we demonstrated in this experiment can be generalized to a wider scale.…”
Section: Effects On Blood Componentsmentioning
confidence: 99%
“…Similar to the enzymatically generated oxysterols that are associated with diets high in cholesterol,41–43 free radical generated oxysterols are produced via consumption of HCHS diets;44 however, they do not act as ligands for LXR. Moreover, recent evidence suggests that free radical generated oxysterols can impede the physiological actions of enzymatic oxysterols 45.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that increasing the ingestion of dietary fat or its saturated fatty acid proportion can induce higher plasma cholesterol levels without largely influencing plasma TG concentrations (Feoli et al, 2003). Thus, it may be the dietary fatty acid profile (Table 1), primarily the level of unsaturation (as shown by the unsaturation index) that had a lowering effect on the total cholesterol level, as also demonstrated in quails (Yuan et al, 1998), chicks (Feoli et al, 2003) and rabbits (Szabó et al, 2004). Interestingly, the change from yolk to feed was matched by a marked increase in the unsaturation of the dietary fatty acid profile.…”
Section: Lipid Metabolitesmentioning
confidence: 92%